Sasanian Persia : the rise and fall of an empire - Daryaee, Touraj, 1967- (I. B. Tauris, 2023)
Of profound importance in late antiquity, the Sasanian Empire is virtually unknown today, except as a counterpoint to the Roman Empire. In this highly readable history, Touraj Daryaee fills a significant gap in our knowledge of world history. He examines the Sasanians' complex and colourful narrative and demonstrates their unique significance, not only for development of Iranian civilization but also for Roman and Islamic history. The Sasanians were the last of the ancient Persian dynasties and are best known as the pre-eminent practitioners of the Zoroastrian religion. Founded by Ardashir l in 224 CE, the Sasanian Empire was the dominant force in the Middle East for several centuries until its last king, Yazdgerd lll, was defeated by the Muslim Arabs in the seventh century. In this concise yet comprehensive book, Touraj Daryaee provides an unrivalled account of Sasanian Persia. Drawing on extensive new sources, he paints a vivid portrait of Sasanian life and unravels the divergent strands that contributed to the making of this great empire. This new edition includes updated economic and political histories as well as several inscriptions that have been found in recent years.